UJI AKTIVITAS ANTIOKSIDAN EKSRTRAK LUMUT HATI (Marchantia polymorpha) - Nurhaeni Nurhaeni; Gladys; Jaya Hardi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
The research is about antioxidant activity of the liverworts (Marchatia polymorpha) extract based on the level of a polar solvent. This research was done by maceration of liverworts by using n-hexane, ethyl acetate and ethanol solvent. The n-hexane, ethyl acetate, and ethanol fraction were tested the antioxidant activity by using DPPH method. The result was obtained for antioxidant activity (IC50) on n-hexane extract, ethyl acetate, ethanol, and vitamin C is 1065.33 ppm, 1326.52 ppm, 1876.11 ppm, and 13.45 ppm, respectively. The liverworts extract was identified contains secondary metabolites compounds of flavonoid, tannins, polyphenol, alkaloid, and steroid. Keywords: Liverwort extract, antioxidant, IC50